Development of Teaching Modules Based on the Independent Learning Curriculum in Islamic Religious Education Subjects in Elementary Schools - Muti, Siti Muti'ah; Makmur, Makmur (South Sulawesi Education Development (SSED), 2025)
This research aims to develop a teaching module based on the Independent Learning Curriculum in Islamic Religious Education class V at UPT SDN 157 Sindu Agung. The method used is development research with the ADDIE model, including the Analysis, Design, Development, and Implementation stages. Module validation is carried out by evaluating material, language, and media experts using validation sheets. The validation results showed the validity level of the module with a percentage of 75% (valid) for the material, 91.6% (very valid) for the language, and 92.8% (very valid) for the media. The practicality of the module based on the educator's questionnaire reached 88.8% (very practical). This teaching module meets the criteria of validity and practicality to be used as an effective teaching material in learning the material